(untitled) (Academia Journal of Medicine, 2024)
The objective is to evaluate the instrumentation time required for primary molar root canal preparation using two pediatric rotary file systems (Kedo-S Plus & Fanta AFTM Baby) in comparison to manual K-files. 60 lower primary molars of healthy youngsters, ages 4-8 years were participated. Three groups (n=20) received a random assignment of molars. Kedo-S Plus and Fanta AFTM Baby rotary systems were used to prepare groups I and II, while a manual K file was used to organise group III, stopwatch was used to estimate the instrumentation time. The result shows that the 78.8 seconds), followed by group II and the manual-K file group (p<0.05). Thus, the tested rotary file systems required less instrumentation time.